The Impact of Marketing Tools on the Recyclables Circulation in the Circular Economy - SADCHENKO, Оlena; ZABALDINA, Yuliia; LIULCHAK, Zoreslava; BUBLYK, Lilia; KANISHCHENKO, Olena (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024DO - 10.14505/tpref.v14.4(32).20, 2024)
Increasing the efficiency of the recyclables circulation is a generally recognized necessity in view of the worsening of environmental problems. In this context, marketing plays an important role as an effective stimulus for the transition to a circular economy. The aim of the study is to determine marketing tools capable of influencing the improvement of the efficiency of the recyclables circulation, in accordance with the determined aspects of green growth. The work used the methods of correlation, regression, and statistical analysis, as well as case studies. The conducted research proved the correlation between the waste recycling rate and all dimensions of green growth. These include increasing the efficiency of resource use, protecting natural capital, developing a green economy, and increasing social inclusion. The regression analysis, where the level of waste recycling was the dependent variable, found a statistically significant effect of social inclusion. This gave grounds to propose a list of marketing tools that could be useful for increasing the efficiency of the recyclables circulation for each of the studied aspects of green growth. This can be useful for developing strategies and approaches depending on specific needs. It is appropriate to use marketing tools determined for this specific direction (information campaigns, etc.), in particular, in case of insufficient efficiency of the recyclables circulation caused by a low level of social inclusion.